Program Sinetron Cinta 2 Pilihan Episode 186 Di SCTV: Analisis Dari Sudut Pandang Regulasi Penyiaran - Muhammad Luthfi Nugraha; Harmonis Harmonis (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
The soap opera "Cinta Dua Pilihan" has become one of the popular shows in Indonesia, although it is not at the top of the rating list for soap operas and television programs. With an intriguing storyline and complex characters, this soap opera has a dedicated fan base that enjoys the love story and intrigues it offers. This research aims to understand the message content and analyze the potential violations of Indonesian broadcasting regulations in episode 186 of the soap opera "Cinta Dua Pilihan," which aired on SCTV on December 4, 2022. Referring to the theory of the Broadcasting Behavior Guidelines and Program Standards (P3SPS) and using Content Analysis method. The results of this research provide a deeper understanding of the importance of strict supervision by broadcasting regulatory bodies in maintaining the quality of television content. Additionally, this research also implies the need for further evaluation of specific television programs to ensure they comply with the values ​​upheld by society and applicable regulations. In the context of intense competition in the Indonesian soap opera industry, this research provides a broader perspective on the role of broadcasting regulation in maintaining the quality of television content and protecting the public from potentially harmful content. Therefore, appropriate action needs to be taken to ensure that television programs continue to comply with the guidelines and regulations that have been established.